2020
DOI: 10.1152/ajplung.00050.2020
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between air-liquid interface cultures and in vivo transcriptomics of nasal brush biopsy

Abstract: Air-liquid interface (ALI) cultures are ex vivo models that are used extensively to study the epithelium of patients with chronic respiratory diseases. However, the in vitro conditions impose a milieu different from that encountered in the patient in vivo, and the degree to which this alters gene expression remains unclear. In this study we employed RNA sequencing to compare the transcriptome of fresh brushings of nasal epithelial cells with that of ALI-cultured epithelial cells from the same patients. We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Exposure to air stimulates the epithelial progenitor cells to differentiate into heterogeneous pseudostratified ciliated, goblet and basal cells, alongside other specialised cell types such as the ionocyte (Montoro et al 2018). After 28 days, this differentiated epithelium exhibits mucus production and motile cilia, and transcriptionally has been shown to strongly correlate (>96% similarity) with the expression profile of epithelial cells obtained from the original nasal brushings from the same patients (Ghosh et al 2020).…”
Section: Models Of the Airwaymentioning
confidence: 84%
“…Exposure to air stimulates the epithelial progenitor cells to differentiate into heterogeneous pseudostratified ciliated, goblet and basal cells, alongside other specialised cell types such as the ionocyte (Montoro et al 2018). After 28 days, this differentiated epithelium exhibits mucus production and motile cilia, and transcriptionally has been shown to strongly correlate (>96% similarity) with the expression profile of epithelial cells obtained from the original nasal brushings from the same patients (Ghosh et al 2020).…”
Section: Models Of the Airwaymentioning
confidence: 84%
“…However, culturing cells at the ALI is a well-established technique [53,54] in cell culture, which stimulates cilia regeneration after the native cilia have been lost [50]. In a recent study, nasal epithelial cells grown in ALI conditions were shown to well-represent their in vivo counterparts in terms of transcriptome and gene expression profile [55]. In another study, culturing nasal epithelial cells on a porous support using the ALI cell culture model stimulated the ciliary differentiation of nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cryopreserved cells were expanded and maintained at an air–liquid interface (ALI) as described previously ( Nishida et al, 2017 ; Ghosh et al, 2020 ). The cryopreserved cells were amplified on rat tail collagen I (Corning, NY, USA)-coated flasks with PneumaCult TM -Ex Plus medium (StemCell Technologies Inc., Vancouver, Canada).…”
Section: Methodsmentioning
confidence: 99%